The executive's guide to 21st century corporate citizenship : how your company can win the battle for reputation and impact - Stangis, Dave; Smith, Katherine Valvoda (Emerald Publishing, 2017)
The Executive's Guide to 21st Century Corporate Citizenship provides a major update on how to 'do' corporate citizenship, showing senior managers how they can win the reputation battle and deliver value to society while creating the most successful business possible in today's competitive landscape.